Investigation to Understand the Co Ions Inclusion in Ba3SnO Antiperovskites Structure - Jafar, Naveed; Murtaza, G.; Nazir, Ghazanfar; Rehman, Adeela (Journal of Materials and Physical Sciences, 2021)
The current research focuses on the fabrication and characterization of barium tin oxide antiperovskite oxide Ba3SnO. BaO and Sn2O were used as precursors to synthesise the Ba3SnO by using solid state ceramic method. Co ion has been implanted using Pelletron Accelerator with different doses 1013, 5×1013, 1014 ions/cm2. The study includes the investigations of penetration depth range of Co ions in the target material, structural, surface morphology, verification of elemental composition, and band gap energy by using the characterization techniques SRIM, XRD, SEM, EDX, FTIR, and UV-Vis spectroscopy respectively. Phase identification of desired material assures by XRD. SEM results showed that the rough and sharp rod shape varies into a very smooth and fine granular shape by ion implantation. EDX plots confirm the existence of basic elements like Ba, Sn, Co and O. The FTIR identify the unknown material and components which confirmed the formation of B3SnO and incorporation of Co ions. UV-Vis spectroscopy results revealed that increasing the implanted ion dose causes a slight increase in band gap energy from 2.61 to 2.88 of this material. The obtained results allow us to conclude that the prepared sample contains a fine structure with no impurity. Therefore, we can say that this process is ideal for obtaining fine structured Ba3SnO.